2014
DOI: 10.1002/anie.201310280
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Gold Acetylides: Synthesis of Vinyl Sulfonates via Gold Vinylidene Complexes

Abstract: Differently substituted terminal alkynes that bear sulfonate leaving groups at an appropriate distance were converted in the presence of a propynyl gold(I) precatalyst. After initial formation of a gold acetylide, a cyclization takes place at the β-carbon atom of this species. Mechanistic studies support a mechanism that is related to that of dual gold-catalyzed reactions, but for the new substrates, only one gold atom is needed for substrate activation. After formation of a gold vinylidene complex, which form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 79 publications
5
46
0
2
Order By: Relevance
“…66 The need for dual activation can be avoided by generating gold alkylidene carbenoids via cyclization onto alkyl sulfonates. 67 Metal vinylidenes such as those described above also undergo reaction with external nucleophiles. Osmium, platinum and ruthenium vinylidenes have been shown to react with H 2 O to form hydroxy carbenes, which then tautomerize to the metal acyl species.…”
Section: Metal Vinylidenesmentioning
confidence: 97%
“…66 The need for dual activation can be avoided by generating gold alkylidene carbenoids via cyclization onto alkyl sulfonates. 67 Metal vinylidenes such as those described above also undergo reaction with external nucleophiles. Osmium, platinum and ruthenium vinylidenes have been shown to react with H 2 O to form hydroxy carbenes, which then tautomerize to the metal acyl species.…”
Section: Metal Vinylidenesmentioning
confidence: 97%
“…The investigation began with synthesis of aldehyde 19 in eight steps from (þ)-sclareolide (14) according to our previously published procedures [6] (Scheme 3). Nucleophilic addition of the aryllithium species generated from aryl bromide 20 [11] and t-BuLi gave alcohol 21 as single diastereomer (although the configuration of the newly formed stereocentre at C-10 was not determined).…”
Section: 18mentioning
confidence: 99%
“…This reaction failed to proceed, perhaps owing to the presence of the unprotected phenol at C-14. We therefore synthesized 34 (a dihydrobenzofuran substrate with a methoxy group instead of a phenol at C-14) via the union of aldehyde 19 and aryl bromide 32 [14] to give alcohol 33, followed by acid-catalyzed ring expansion (Scheme 5). Basic fragmentation of 34 with sodium pentoxide was possible, but we were unable to control the location of the newly formed alkene, with the undesired conjugated diene 35 formed as a 1 : 1 mixture of atropisomers (owing to restricted rotation about the C-10-C-12 bond).…”
Section: 18mentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the formation of gold vinylidene intermediates 103 is also possible by the cyclization of gold acetylides alone and therefore not strictly dependent on a dual activation mode. The protocol can be utilized to synthesize tetrahydrofuran or pyrrolidine derivatives bearing a vinyl sulfonate moiety 104 from readily available substituted alkynyl sulfonates 102 (Scheme 12.47) [51].…”
Section: Synthesis Of O-heterocycles and N-heterocyclesmentioning
confidence: 99%